The Transformation of the Thai Economic Systems of Trading from Sukhothai period until Early Rattanakosin Period. - เกาศล ณัฐกานต์ (Chophayom Journal, 2019)
The economic system of sea transaction from Sukhothai period to early Rattanakosin period was transformed according to the social status of the country. During Sukhothai period, the economic system was a self-reliant system. The main focus was on agriculture. Then people started to have a transaction with foreigners in Ayutthaya period and the economic system in this time was monopoly under national treasury. In early Rattanakosin period, free trade system was used. Therefore, the transformation of the economic system of trading of each period reflected the social status of Thailand during each of those periods. Keywords : Economy system of trading, Sukhothai period, Ayutthaya period, Early Rattanakosin period